'Ghetto language' in Danish mainstream rap. (January 2017) - Stæhr, Andreas; Madsen, Lian Malai
Abstract: In this article, we carry out an ethnographically informed sociolinguistic analysis of language use in contemporary Danish rap. We contextualize our analytical observations by drawing on knowledge from interviews with stakeholders from the music industry and ethnographic fieldwork carried out among a group of young rappers. Based on this research, we argue that while current Danish rap may be innovative and renew the way language is used compared to the linguistic tendencies of the Danish hip hop market before 2013 it does not expand the way language as such is talked about, but to some extent reproduces existing value ascriptions. Highlights: Current Danish rap is renews language use with urban vernacular resources. Majority Danes are integrated into multicultural communities through language. The hip hop speech style is becoming enregistered with youth, not minority. The current Danish rap does not expand the way language is talked about.